INTEGRATION OF INDIAN KNOWLEDGE SYSTEMS (IKS) INTO STEM EDUCATION: A SURVEY STUDY OF AWARENESS, ATTITUDES AND PRACTICES AMONG PRE-SERVICE AND IN-SERVICE TEACHERS - Dhananjay Joshi; Bansal, Tulika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India’s educational and scientific heritage spans thousands of years, with notable contributions in many fields such as mathematics, astronomy, metallurgy, medicine, architecture, agriculture and environmental conservation. This entire knowledge is called the Indian Knowledge Systems (IKS). The National Education Policy (NEP) 2020 emphasizes the integration of IKS into formal education, especially in science, technology, engineering and mathematics (STEM) education, so that students’ learning experience is contextualized, multidisciplinary and culturally connected. However, the role of the teacher is paramount in the successful implementation of any educational reform. The policy objective will be achieved only if teachers are aware of IKS, have a positive attitude and are able to implement it in the classroom. Against this backdrop, this survey-based research was conducted to assess awareness, attitude and practical integration of IKS among pre-service and in-service STEM teachers. A descriptive survey design was used in this study. The sample was 200 participants (100 pre-service and 100 in-service STEM teachers) selected by purposive sampling from five states—Delhi, Uttar Pradesh, Maharashtra, Tamil Nadu and Assam. The IKS–STEM Awareness and Integration Index (α = 0.87) was used for data collection, which had three subscales: (1) awareness (10 questions, 0–50 marks), (2) attitude (10 questions, 0–50 marks), (3) behaviour/practice (5 questions, frequency in the past month). Data were analyzed using descriptive statistics, independent t-tests, and Pearson correlation in Excel. The results showed that overall teachers had a moderate level of awareness of IKS (M = 32.8, SD = 6.4) and a high level of attitude (M = 43.2, SD = 5.7). In-service teachers scored statistically higher than pre-service teachers in awareness (t = 3.42, p < .01), while no significant difference was found in attitude and behavior. A moderate positive correlation (r = .46, p < .01) was found between awareness and behavior. The study indicates that although attitudes towards IKS are very positive, its actual classroom use is limited. This is mainly due to the lack of curriculum-oriented materials and practical teaching strategies. This research concluded that inclusion of IKS examples in textbooks, development of open-source resource banks and collaborative platforms for teachers are essential to achieve the goals of NEP 2020.